Aboio no sertão paraibano: um canto no trabalho, um trabalho no canto. - Mendes, Adriano Caçula (2015)
This work results from a research about Aboio’s (cow herding) singing in the Paraiba’s high sertão (backwoods) region, especially in these cities: Sousa, Cajazeiras, Marizópolis, São João do Rio do Peixe among surrounding municipalities. The focus is on the adaptive processes that this kind of chanting undergoes in order to survive as a manifestation of the Vaqueiros’ (Cowboy) voice and culture. Interviews and ethnographic research has been done with Aboio’s singers of this region seeking for an understanding of musical and sociological changes that have occurred to cowboy culture and how they influence and construct reality for contemporary cowboy. It follows that the aboio, actually, is very different from that described by Mário de Andrade since he organized the folkloric research missions in 1938. The aboio has adapted to new contexts and to the changes brought by modernity and late modernity in order to ensure its survival in northeast backcountry culture.